The Effects of Using Pineapple Stem Starch as an Alternative Starch Source and Ageing Period on Meat Quality, Texture Profile, Ribonucleotide Content, and Fatty Acid Composition of Longissimus Thoracis of Fattening Dairy Steers - Chanporn Chaosap; Katatikarn Sahatsanon; Ronachai Sitthigripong; Suriya Sawanon; Jutarat Setakul (Foods, 2021)
< 0.05) in contrast to meat from steers fed PI, which had the lowest oleic acid but the highest erucic acid. Steers fed CO appeared to produce healthier meat as this was positively associated with monounsaturated fatty acid content. Meat from steers fed PI had higher levels of IMP, which may be associated with good taste.
Keywords: Meat and Animal Product Quality; Animal Nutrition and Physiology; Aquaculture Nutrition and Growth